Disc tearing leads to low and high frequency quasi-periodic oscillations in a GRMHD simulation of a thin accretion disc. Issue 2 (28th November 2022) - Musoke, G; Liska, M; Porth, O; van der Klis, Michiel; Ingram, Adam
ABSTRACT: Black hole X-ray binaries (BHXRBs) display a wide range of variability phenomena, from long duration spectral state changes to short-term broad-band variability and quasi-periodic oscillations (QPOs). A particularly puzzling aspect is the production of QPOs, which – if properly understood – could be used as a powerful diagnostic tool of black hole accretion and evolution. In this work, we analyse a high-resolution 3D general relativistic magnetohydrodynamic simulation of a geometrically thin accretion disc, which is tilted by 65° with respect to the black hole spin axis. We find that the Lense–Thirring torque from the rapidly spinning 10 M ⊙ black hole causes several sub-discs to tear off within ∼10–20 gravitational radii. Tearing occurs in cycles on time-scales of seconds. During each tearing cycle, the inner sub-disc precesses for 1–5 periods before it falls into the black hole. We find a precession frequency of $\sim 3\rm Hz$, consistent with observed low-frequency QPOs. In addition, we find a high frequency QPO (HFQPO) with centroid frequency of ∼55 Hz in the power spectra of the mass-weighted radius of the inner disc and the radial mass flux. This signal is caused by radial epicyclic oscillations of a dense ring of gas at the tearing radius, which suggests a corresponding modulation of the X-ray light curve and may thus explain some of the observed HFQPOs.